Pendampingan manajemen pencegahan anemia pada remaja - Desi Oktariana; Evi Lusiana; Nia Savitri Tamzil; Gita Dwi Prasasty (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Anemia is a condition characterized by a reduction in the number of red blood cells and / or hemoglobin (Hb) concentration. The prevalence of anemia in Indonesia ranges between 12% in adolescent boys and 23% in adolescent girls with the proportion of anemia in the age group of 15-24 years and 25-34 years. Knowledge of the level and causes of anemia in adolescence is very is important, because it is a window of opportunity for school-based interventions to improve adolescent health. The purpose of this activity is to increase the awareness of adolescent about the importance of preventing anemia, as well as improving the skills of UKS member in carrying out activities that are preventive and promotive towards preventing anemia among adolescents. The method used is to provide counseling, blood checks, and provide training and assistance to health cadres in schools to carry out activities that are preventive and promotive to students in schools. The results obtained from this activity are an increase in students' knowledge about anemia, as well as preventive and promotive measures to prevent it.